The Influence of Green Marketing on Starbucks Purchase Decisions in Palembang - Viodita Amanda Salsabilla; Yulia Hamdaini Putri; Hera Febria Mavilinda (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study aims to examine the influence of green marketing on consumer purchasing decisions at Starbucks in Palembang. Methodology/approach: The research was conducted at Starbucks outlets in Palembang, Indonesia, using a quantitative approach and purposive sampling. Data were collected from 175 respondents through questionnaires and analyzed using multiple linear regression with SPSS version 25. Results/findings: The results show that six out of seven green marketing dimensions namely product, price, place, promotion, process, and physical evidence significantly affect purchasing decisions. The people dimension does not show a significant influence. Simultaneously, all seven dimensions significantly influence purchasing behavior, indicating that consistent implementation of green marketing strategies can strengthen consumer trust and encourage environmentally responsible buying.behavior. Conclution: Green marketing has a significant role in shaping consumer purchasing decisions, highlighting its potential as an effective strategy for businesses aiming to promote sustainability. Limitations: This study is limited to one brand and location, which may not fully represent consumer behavior in different regions or with different types of businesses. Contribution:The study contributes to marketing and sustainability literature by providing empirical evidence on how green marketing strategies impact purchasing decisions in the context of the service industry.